Increasing Hydrogen Production Efficiency of N2-Fixing Cyanobacterium Anabaena siamensis TISTR 8012 by Cell Immobilization - Taikhao, Samart; Phunpruch, Saranya (My University, 2017)
H2 produced by cyanobacteria is one of the interesting alternative energy carriers for the future. The filamentous N2-fixing cyanobacterium Anabaena siamensis TISTR 8012 is a potential microorganism for H2 production. It can produce H2 via both photosynthesis and nitrogen fixation processes. This study aimed to increase the efficiency of H2 production by immobilization of A. siamensis cells. The result showed that H2 production rate by A. siamensis grown in BG110 medium was higher than that in BG11 and Allen-Arnon media due to an increase of the heterocyst cells. The sulfur deprivation during adaptation period for 24 hours increased its H2 production rate. The optimal conditions for H2 production by immobilized cells were immobilization with alginate and using 150 gel beads in 20 mL glass vial. In immobilized cells, an addition of 0.5% fructose resulted in a 2-fold increase of H2 production rate. Finally, the reducing agents β-mercaptoethanol and methylviologen enhanced H2 production rate with 3.092 and 2.426 μmolH2 mg chl a-1 h-1, respectively, in A. siamensis immobilized cells whereas NADH, dithiothreitol and sodium dithionite were not capable of increasing H2 production rate.
Keywords: Anabaena siamensis; cell immobilization; hydrogen production